Implementation of Learning the History of Islamic Culture Through Animated Videos on The Story of The Prophet Muhammad Shalallaahu 'Alayhi Wasallam - Mustamik, Mustamik; Fatimah, Meti; Subando, Joko (Abjadia : International Journal of Education, 2025)
This study aims to describe the implementation strategy of Islamic Cultural History learning using animated video media on the story of the Prophet Muhammad SAW at the Muhammadiyah Kismoyoso Ngemplak Boyolali Elementary School, and to evaluate the influence of the media on students' interest and understanding. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study showed that learning was carried out in a structured manner through the stages of apperception, video screening, interactive discussion, and value reflection. The animated video media used was by the curriculum had attractive visuals and easy-to-understand narratives, so it was able to increase students' attention and focus. In addition, the use of animated videos encouraged students' active participation in discussions and facilitated understanding and memorisation of the material, including the application of Islamic values in everyday life. In conclusion, animated videos are an effective medium in improving the quality of Islamic Cultural History learning and students' learning motivation.